Implementation of Short Hadith Memorization Learning Through the Hand Movement Method at BA Aisyiyah Ketandan II in the 2023/2024 Academic Year - Sari, Rizna Aisyah Rahma; Tanfidiyah, Nur (Departement of PAI, Universitas Majalengka, 2025)
The research background is that there is something unique about learning to memorize hadiths, namely using the hand movement method, in practice children become more active. The use of this hand movement method is different so it needs to be researched. The aim of the research was to determine the implementation of learning to memorize short hadiths through hand movements at BA Aisyiyah Ketandan II Karangnongko Ketandan Klaten. This research uses a qualitative descriptive research method. Data collection techniques use observation, interviews, and documentation, then the data analysistechniques used are data condensation, data collection, data presentation, and drawing conclusions. The research results show that the strategy for learning to memorize short hadiths using the hand movementmethod has 4 stages. In the first stage of introduction, yhe teacher carries out an ice breaking game to change the atmosphere. In secon stage of preparation, the teacher prepares the RPPH that has been made, and learns to memorise short hadiths through movement methods according to the theme. In the third stage of presenting the lesson discussion, the teacher prepares the learning instruments and media used. The fourth stage is application and evaluation. There are 3 activities in the application stage, namely opening, core and closing. In the opening, the teacher starts with greetings, introduces the prophet until the children understand that the prophet is a good example, then the core learning activity is memorizing hadiths according to the theme of each school, telling a story fuul of wisdom abot the morality of the prophet, reading the hadith that will be taught previously with the sentenv“Qaala Rasulullahi Salallahu ‘Alaihi Wasallam”or “Rasulallah Salallahu ‘alaihi Wasallam said”. The teacher reads the selected hadith accordig to the plan accompanied by appropriate. hand movements. Closing activity, the teacher does recalling. Learning evaluation is carrid out using a checklist according to the hadith memorization achievements based on the memorization achivements each semester.